1998
DOI: 10.1128/mcb.18.1.233
|View full text |Cite
|
Sign up to set email alerts
|

CIF150, a Human Cofactor for Transcription Factor IID-Dependent Initiator Function

Abstract: The transcription factor IID (TFIID) complex is highly conserved between the Drosophila and mammalian systems. A mammalian homolog has been described for all the Drosophila TATA box-binding protein-associated factors (TAFs), with the exception of dTAF(II)150. We previously reported the identification of CIF, an essential cofactor for TFIID-dependent transcription from promoters containing initiator (Inr) elements. Here we describe the molecular cloning of CIF150, the human homolog of dTAF(II)150, and present b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
66
4
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 38 publications
3
66
4
1
Order By: Relevance
“…First, there is considerable evidence that TFIID binds to the Inr in a sequence-specific manner (e.g., see Kaufmann and Smale 1994;Martinez et al 1994;Purnell et al 1994;Burke and Kadonaga 1996;Oelgeschläger et al 1996). More specifically, it appears that TAF II 150 and TAF II 250 (i.e., TAF2 and TAF1; Tora 2002) are the key subunits of TFIID that interact with the Inr (Verrijzer et al 1994(Verrijzer et al , 1995Kaufmann et al 1998;Chalkley and Verrijzer 1999). Aside from TFIID binding to the Inr, it has also been observed that purified RNA polymerase II (or RNA polymerase II along with TBP, TFIIB, TFIIF) is able to recognize the Inr and to mediate transcription in an Inr-dependent manner in the absence of TAFs (Carcamo et al 1991;Weis and Reinberg 1997).…”
Section: The Initiator (Inr)mentioning
confidence: 99%
“…First, there is considerable evidence that TFIID binds to the Inr in a sequence-specific manner (e.g., see Kaufmann and Smale 1994;Martinez et al 1994;Purnell et al 1994;Burke and Kadonaga 1996;Oelgeschläger et al 1996). More specifically, it appears that TAF II 150 and TAF II 250 (i.e., TAF2 and TAF1; Tora 2002) are the key subunits of TFIID that interact with the Inr (Verrijzer et al 1994(Verrijzer et al , 1995Kaufmann et al 1998;Chalkley and Verrijzer 1999). Aside from TFIID binding to the Inr, it has also been observed that purified RNA polymerase II (or RNA polymerase II along with TBP, TFIIB, TFIIF) is able to recognize the Inr and to mediate transcription in an Inr-dependent manner in the absence of TAFs (Carcamo et al 1991;Weis and Reinberg 1997).…”
Section: The Initiator (Inr)mentioning
confidence: 99%
“…CIF150 protein shows striking homology to the Drosophila TAF II 150 protein (dTAF II 150) and some similarity to the essential yeast protein TSM-1 (18,36,47). More re-cently, essentially the same cDNA was cloned independently by Martinez and colleagues and named human TAF II 150 (hTAF II 150) (23).…”
mentioning
confidence: 99%
“…Even more surprising is the discovery that one subset of TAF II s in the TFIID complex is also an integral component of histone acetylase complexes connecting the polymerase II machinery with chromatin-modifying activities (8,27,30). A better understanding of TAF II function in core promoter recognition and activation requires additional comprehensive in vivo analysis.We reported the identification of an essential cofactor for TFIID-dependent Inr function, CIF150 (cofactor of Inr function) (17,18). CIF150 protein shows striking homology to the Drosophila TAF II 150 protein (dTAF II 150) and some similarity to the essential yeast protein 36,47).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian promoters, the Inr consensus sequence is Py-Py-A ϩ1 -N-T/APy-Py (where A ϩ1 is the transcription start site) (3,20,39), whereas in Drosophila promoters, the Inr consensus is T-C-A ϩ1 -G/T-T-T/C (1,18,32). It has been found that TAF II 150 and TAF II 250 play a role in the binding of TFIID to Inr elements (8,16,21,42,44).…”
mentioning
confidence: 99%